2015
DOI: 10.4236/ijohns.2015.41005
|View full text |Cite
|
Sign up to set email alerts
|

Triple-c Cartilage Tympanoplasty: Case Series

Abstract: The triple-c cartilage tympanoplasty i.e. (composite chondroperichondrial clip) technique was devised by Fernandes in 2003. Objectives: The objective of our case series was to assess the success rate and efficacy of the triple-c cartilage tympanoplasty by transcanal approach. Study Design: A retrospective analysis of patients subjected to the technique was conducted. Methods: 20 cases who met the inclusion criteria were assessed by otomicroscopy and pure tone audiometry before and 2 months after the surgery. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…All our patients underwent myringoplasty using temporalis fascia graft. There are several studies which suggest tragal cartilage and perichondrium graft placed as a butterfly fashion is equally efficient as a graft for myringoplasty during endoscopic technique [17,18]. Further studies are required using the autologous tragal chondro-perichondrial graft.…”
Section: Discussionmentioning
confidence: 99%
“…All our patients underwent myringoplasty using temporalis fascia graft. There are several studies which suggest tragal cartilage and perichondrium graft placed as a butterfly fashion is equally efficient as a graft for myringoplasty during endoscopic technique [17,18]. Further studies are required using the autologous tragal chondro-perichondrial graft.…”
Section: Discussionmentioning
confidence: 99%
“…This transfers the acoustic energy better than normal cartilage. 7 Studies by Gierek et al and Couloinger et al have proven that there is no significant hearing difference between the use of temporalis fascia and cartilage for myringoplasty. 25,26 The composite chondro-perichondrial -clip‖ myringoplasty using the tragal cartilage and transcanal approach has a lot of advantages such as its a minimally invasive surgery done transcanally with an endoscope, it can be done in less than 30 minutes duration, it has good postoperative results in the form of perforation closure and improvement in hearing and it is cost-effective as it can be done under local anaesthesia and there is reduced hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…There is very limited data regarding curling of the cartilage, four incisions of the perichondrium -the anti-curling incisions‖ have been described by Tos but a systematic study is still required to validate them. 7 Recent studies show no difference in hearing results between the full thickness and partial thickness grafts 7 . Also histomorphological studies of cartilage grafts of Hitari have shown that there is wide replacement of the chondrocytes by fibrous tissue and loss of lipid vacuoles over time which makes the cartilage graft more homogenous in nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Although our entire patients underwent myringoplasty using temporalis fascia graft, there are many other studies where tragal cartilage and perichondrium grafts were used. 17,18 There has also been studied where only 0 degree scopes are used and other studies were 0, 30 and 70 degree scopes have been used. 1,5 We have used only 0 and 30 degree scopes for our procedure and it has given us the capability to negotiate the curvy external auditory canal.…”
Section: Discussionmentioning
confidence: 99%